OPPORTUNITIES FOR DEVELOPING AN INCLUSIVE MODEL OF SOCIAL ENTREPRENEURSHIP BASED ON FOREIGN EXPERIENCE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article examines the opportunities for developing an inclusive model of social entrepreneurship based on international experience. The study analyzes the theoretical foundations of inclusive social entrepreneurship and explores successful practices implemented in various countries. Particular attention is devoted to the role of social enterprises in promoting social inclusion, reducing inequality, supporting vulnerable populations, and fostering sustainable community development. The research investigates institutional, legal, economic, and social factors that contribute to the effectiveness of inclusive social entrepreneurship models. Through comparative analysis of international experiences, the study identifies key mechanisms that can be adapted to strengthen inclusive social entrepreneurship in developing economies. The findings demonstrate that inclusive social entrepreneurship serves as an effective instrument for enhancing social cohesion, expanding economic participation, and promoting sustainable development. The article concludes that the integration of international best practices with local socio-economic conditions can significantly improve the effectiveness of social entrepreneurship initiatives.